GENETIC DIVERSITY OF S3 MAIZE GENOTYPES RESISTANT TO DOWNY MILDEW BASED ON SSR MARKERS - Amran Muis; Nurnina Nonci; Marcia B. Pabendon (Indonesian Journal of Agricultural Science, 2015)
The compulsory requirement for releasing new high yielding maize varieties is resistance to downy mildew. The study aimed to determine the level of homozygosity, genetic diversity, and  genetic distance of 30 S3 genotypes of maize. Number of primers to be used were 30 polymorphic SSR loci which are distributed over the entire maize genomes. The S3 genotypes used were resistant to downy mildew with homozygosity level of >80%, genetic distance between the test and tester strains >0.7, and anthesis silking interval (ASI) between inbred lines and tester lines was maximum 3 days. The results showed that 30 SSR primers used were spread evenly across the maize genomes which were manifested in the representation of SSR loci on each chromosome of a total of 10 chromosomes. The levels of polymorphism ranged from 0.13 to 0.78, an average of 0.51, and the number of alleles ranged from 2 to 8 alleles per SSR locus, an average of 4 alleles per SSR locus. The size of nucleotides in each locus also varied from 70 to 553 bp. Cophenetic correlation value (r) at 0.67 indicated that the Unweighted Pair-Group Method Using Arithmetic Averages (UPGMA) was less reliable for differentiating genotypes in five groups. Of the total of 30 genotypes analyzed, 17 genotypes had homozygosity level of >80% so it can be included in the hybrid assembly program.